Antenna for 5G Mobile Communication at 28 GHz - Razak, Noor Syazwani; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2022)
Fifth generation (5G) mobile communications has become one of the trendiest issues in recent years, especially in the development of wireless technology for communications. As such, 5G mobile communications will also suffer severe path loss, due to the high frequency bands. This work presents the antennas for 5G mobile communication at 28 GHz on Rogers RT5880 with a dielectric constant, ?r of 2.2, loss tangent, tan ? of 0.0009 and thickness, h of 0.787 mm. A rectangular microstrip patch are proposed in this work which consist of a single element and array configurations with two and four elements. Microstrip feed line and inset feed line are implemented to observe their performances. It can be observed from the simulation results that the gain and directivity increase from a single element up until four elements array antenna for both the microstrip feed line and inset feed line of the rectangular microstrip patch antenna. This confirm to the fact that array antenna produces high gain and directivity which could overcome the challenge of high free space path loss in millimeter-wave. The spacing between each element in the array antenna are spaced accordingly and not so close with each other in order to suppress the mutual coupling between the elements. It is shown that the mutual coupling is greatly reduced based on the greater values of reflection coefficient in two-element and four-element array antennas. Based on the gain, directivity and reflection coefficient, inset feed line antennas perform better than microstrip feed line antennas. In terms of dimensions, the size of the antenna with an inset feed line reduces as compared to microstrip feed line as the number of elements increases. Thus, it is safe to conclude that inset feed line antennas outperform microstrip feed line antennas when it comes to gain, directivity, reflection coefficient, and dimensions of antennas. Therefore, the proposed array antennas in this work are suitable to be used in 5G mobile communications.